COMMENTS ON THE ARTICLE BY A.YU. ASANOV, L.S. NAMAZOVA, V.G. PINELIS, N.V. ZHURKOVA, N.I. VOZNESENSKAYA «GENETIC FOUNDATIONS OF THE BRONCHIAL ASTHMA» - A.Yu. Asanov (Union of pediatricians of Russia, 2008)
.